Pengaruh Harga, Kualitas Produk dan Pendapatan Terhadap Minat Beli Sayuran Hidroponik di PT. Kebunsayur Surabaya - Fadhilah, Sulthan Auliya' Zhafran; Winarno, Sri Tjondro; Wijayati, Prasmita Dian (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
PT. Kebunsayur Surabaya, an agribusiness company producing hydroponic vegetables, always maintains prices that are appropriate for their products. The company also ensures the quality of their products so that consumers are not disappointed when purchasing. Additionally, the company adjusts the prices for each type of hydroponic vegetable they produce according to consumer income, making the products accessible to all segments of society. This research aims to analyze how price influences the purchase interest in hydroponic vegetables at PT. Kebunsayur Surabaya, analyze the influence of product quality on the purchase interest in hydroponic vegetables at PT. Kebunsayur Surabaya, and analyze the influence of income on the purchase interest in hydroponic vegetables at PT. Kebunsayur Surabaya. The analytical method used is Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with Warp PLS 8.0 software. Primary data was collected through questionnaires and interviews. The sample consisted of 50 respondents determined through purposive sampling technique. The results of the study indicate that price has a positive and significant influence, product quality has a positive and significant influence, and income has a positive and significant influence.